Observations on Jensen's Experimental Design for Study of Effects of Accounting Variations in Decision Making - Dyckman, Thomas R. (Journal of Accounting Research, 1967)
Thomas R. Dyckman, Observations on Jensen's Experimental Design for Study of Effects of Accounting Variations in Decision Making, Journal of Accounting Research, Vol. 5, No. 2 (Autumn, 1967), pp. 221-229